2007
DOI: 10.1007/s00586-007-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cervical myelopathy in patients with the fibromyalgia syndrome: outcomes and implications

Abstract: Some patients with fibromyalgia also exhibit the neurological signs of cervical myelopathy. We sought to determine if treatment of cervical myelopathy in patients with fibromyalgia improves the symptoms of fibromyalgia and the patients' quality of life. A non-randomized, prospective, case control study comparing the outcome of surgical (n = 40) versus non-surgical (n = 31) treatment of cervical myelopathy in patients with fibromyalgia was conducted. Outcomes were compared using SF-36, screening test for somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…Six studies, four of which were CCTs, were identified which examined surgery versus non-surgical interventions in patients with radiculopathy [12][13][14][15][16][17]. Three studies, of which two CCTs, compared surgery versus nonsurgical interventions in myelopathy patients [18,19,20]. The RCT also reported the 10-year follow-up data [21].…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies, four of which were CCTs, were identified which examined surgery versus non-surgical interventions in patients with radiculopathy [12][13][14][15][16][17]. Three studies, of which two CCTs, compared surgery versus nonsurgical interventions in myelopathy patients [18,19,20]. The RCT also reported the 10-year follow-up data [21].…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…All six CCTs were identified with a high risk of bias (Table 2) [12,13,14,17,19,20]. Two out of three RCTs also had a high risk of bias.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] It has been reported that FM is more prevalent in female patients with AS, and it has also been found to be correlated with the BASDAI and BASFI. [19,20] Azevedo et al [20] reported that six out of 17 women in their study had FM, whereas only five out of 54 men were afflicted.…”
Section: Discussionmentioning
confidence: 95%